Gender power walk - Caroli, Giulia; Penel, Charlotte; Maviza, Gracsious; Jaskolski, Tina (2025)
The Gender Power Walk is an active role-playing exercise in which participants physically move across a room to represent their assigned character’s position within gendered power dynamics. Participants first engage in the role-play walk, followed by a facilitated group discussion to discuss why people are positioned in certain places in the room relative to other participants, with the aim of unpacking how certain characters are more vulnerable or more resilient in the face of climate impacts on peace and security.